Exploring Experienced Teachers’ Constructions of Culturally and Linguistically Diverse Students in an Online Class - Warren, Amber N. (International Journal of Multicultural Education, 2018)
This article examines online discussions during a teacher education class for experienced teachers seeking licensure in teaching English learners. It seeks to understand experienced teachers’ constructions of culturally and linguistically diverse (CLD) students. Using discourse analysis to emphasize talk as situated and action-oriented, the article indicates how belief claims expressed during experienced teachers’ online discussions construct specific versions of what it means to be a CLD student. Findings further suggest that participants managed their authority to speak about students’ needs in patterned ways. These findings have implications for teaching and learning, particularly for the preparation of experienced teachers.